2011
DOI: 10.1074/jbc.m110.203927
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Two Activation Domains in Zap1 in the Response to Zinc Deficiency in Saccharomyces cerevisiae

Abstract: Previous studies suggested that the zinc-responsive Zap1 transcriptional activator directly regulates the expression of over 80 genes in Saccharomyces cerevisiae. Many of these genes play key roles to enhance the ability of yeast cells to grow under zinc-limiting conditions. Zap1 is unusual among transcriptional activators in that it contains two activation domains, designated AD1 and AD2, which are regulated independently by zinc. These two domains are evolutionarily conserved among Zap1 orthologs suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…In zap1 mutant cells, UBI4 induction occurs during zinc limitation, but this effect is no longer dependent on the ZREs. This result is consistent with our previous observation that Hsf1 activity is increased in zinc-deficient zap1 mutants, which experience a much greater degree of stress than do wild-type cells (32).…”
Section: Reduction Of Proteasome Activity Suppresses the Ubi4⌬supporting
confidence: 82%
“…In zap1 mutant cells, UBI4 induction occurs during zinc limitation, but this effect is no longer dependent on the ZREs. This result is consistent with our previous observation that Hsf1 activity is increased in zinc-deficient zap1 mutants, which experience a much greater degree of stress than do wild-type cells (32).…”
Section: Reduction Of Proteasome Activity Suppresses the Ubi4⌬supporting
confidence: 82%
“…The growing number of unique eukaryotic zinc-regulated factors that have been identified suggests that novel zinc-sensing domains may have evolved independently in different species. Intriguingly, studies with Zap1 have shown that AD1 is plays a primary role in activating genes required to maintain zinc homeostasis, whereas AD2 plays a more major role in gene regulation when zinc deficiency is combined with other environmental stresses (26). Thus, one potential explanation for the diversity in zinc-regulated factors is that each unique factor is able to optimally sense changes in zinc levels under normal and specialized environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Zap1 contains multiple domains that are independently regulated by zinc (25). These domains include AD1, a transactivation domain that is rich in histidine and cysteine residues, and AD2, a transactivation domain that contains a unique regulatory zinc finger pair motif (26). In mammals, MTF-1 also contains multiple zinc-regulated domains including a zinc-responsive DNA binding domain containing six C 2 H 2 -type zinc fingers (9).…”
Section: Discussionmentioning
confidence: 99%
“…Both factors contain multiple zinc-responsive domains. Zap1 contains two transactivation domains that are independently regulated by zinc (9,10). Zinc also inhibits Zap1 DNA binding activity (11).…”
mentioning
confidence: 99%